1990
DOI: 10.1111/j.1365-2125.1990.tb03603.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temazepam on blood pressure regulation in healthy elderly subjects.

Abstract: 1. Blood pressure regulation was studied in 12 healthy elderly subjects after double‐blind randomised administration of placebo, 15 mg and 30 mg temazepam at 10.00 h and 22.00 h. 2. Supine and standing heart rate and blood pressure were measured after daytime administration and supine measurements were obtained during sleep. 3. Temazepam caused a fall in systolic blood pressure and an increase in heart rate after morning administration. These changes were greater in the standing position and were dose‐dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In the pretolerant condition, the gradual increase in heart rate across the afternoon was equivalent to the placebo condition. Although temazepam has been shown to increase heart rate at doses ranging from 5 to 30 mg (7,17), it is notable that, in this study as well as a previous study in our laboratory (8), acute temazepam administration did not appear to have significant cardiac effects. However, this discrepancy may reflect different experimental protocols used.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In the pretolerant condition, the gradual increase in heart rate across the afternoon was equivalent to the placebo condition. Although temazepam has been shown to increase heart rate at doses ranging from 5 to 30 mg (7,17), it is notable that, in this study as well as a previous study in our laboratory (8), acute temazepam administration did not appear to have significant cardiac effects. However, this discrepancy may reflect different experimental protocols used.…”
Section: Discussioncontrasting
confidence: 46%
“…This association is highlighted by the differential changes in body temperature resulting from the administration of either sedative/hypnotics or alerting agents. In the case of somnogenic agents such as melatonin (1,6), adenosine (21,23), adenosine agonists (23), and benzodiazepines (7,17), an extensive body of evidence has demonstrated that these agents increase sleepiness while decreasing core body temperature. In contrast, agents such as caffeine, amphetamines, nicotine, and cocaine decrease sleepiness and increase body temperature (11).…”
mentioning
confidence: 99%
“…HR after DZP administration can inform us indirectly about this issue. Previous studies examining the Bz effect on HR, a marker of heat production in humans (Gilbert et al, 1999;Krauchi et al, 1997;Krauchi and Wirz-Justice, 1994), have yielded inconsistent findings (Ford et al, 1990;Matejcek et al, 1983vs Gilbert et al, 1999Pleuvry et al, 1980) related to HR after administration of temazepam, a clinically used Bz hypnotic. We observed a statistically significant dosedependent increase in HR after DZP administration in subjects taking the 10-mg dose.…”
Section: Commentmentioning
confidence: 99%
“…In comparison, cognitive impairment only increased fall risk by a factor of 5.0 (95% CI=1.8–13.7) and multiple balance and gait abnormalities by a factor of 1.9 (95% CI=1.0–3.7). Sedatives can impair posture, reaction time, coordination, protective responses during falls, and cardiovascular reflexes that normally prevent orthostatic hypotension, 10–12 but much of the measured effect of sedative use also may be attributable to unmeasured health conditions and practices common in sedative users—including comorbidities, decreased coordination, cognitive dysfunction, impaired mobility, and sedative polypharmacy—rather than to a causative link between single sedative use and falls or hip fracture 13–15 …”
mentioning
confidence: 99%